2001
DOI: 10.1021/jo015778x
|View full text |Cite
|
Sign up to set email alerts
|

Catalyzed Reformatsky Reactions with Ethyl Bromofluoroacetate for the Synthesis of α-Fluoro-β-hydroxy Acids

Abstract: The presence of catalytic amounts of CeCl(3) improves yields and simplifies procedure in the Reformatsky reactions of ethyl bromofluoroacetate with aldehydes and ketones to generate diastereomeric mixtures of alpha-fluoro-beta-hydroxy esters, some of which can be separated by crystallization or column flash chromatography. Diastereomerically pure alpha-fluoro-beta-hydroxy acids are obtained by mild alkaline hydrolysis of the resolved alpha-fluoro-beta-hydroxy esters. Detailed NMR data of new alpha-fluoro-beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 27 publications
2
11
0
1
Order By: Relevance
“…[16] Typically, 25, 50, 100 or 200 μmol of substrate was reacted in water/methanol with either isopropyl alcohol or glucose/glucose dehydrogenase for co-factor recycling. [28,31] The anti and syn configuration exhibit characteristic three-bond 19 F-1 H couplings of 17.8 and 22.1 Hz, respectively, which aids in identification. Crude products were analyzed by quantitative 19 F NMR spectroscopy to assess diastereomeric ratio (anti:syn ratio) and percent conversion, which were typically 86-97 % isolated yields.…”
Section: Resultsmentioning
confidence: 99%
“…[16] Typically, 25, 50, 100 or 200 μmol of substrate was reacted in water/methanol with either isopropyl alcohol or glucose/glucose dehydrogenase for co-factor recycling. [28,31] The anti and syn configuration exhibit characteristic three-bond 19 F-1 H couplings of 17.8 and 22.1 Hz, respectively, which aids in identification. Crude products were analyzed by quantitative 19 F NMR spectroscopy to assess diastereomeric ratio (anti:syn ratio) and percent conversion, which were typically 86-97 % isolated yields.…”
Section: Resultsmentioning
confidence: 99%
“…No traces of rearranged or diastereomeric fluorinated products have been detected in the crude product mixture by 19 F NMR spectroscopy. This shows that this ring opening is an S N 2-process favoring the formation of the fluorohydrin with fluorine in the less hindered primary position (Scheme 52) [144].…”
Section: Synthesis By Nucleophilic Ring Opening Of Epoxidesmentioning
confidence: 93%
“…Ten years ago Shen and Qi reported that the Reformatsky reaction of ethyl chlorofluoro acetate with aldehydes in the presence of catalytic amounts of lanthanide salts in dimethylacetamide (DMA) as the solvent provided high yields of the desired fluorohydrins, while the reactions with ketones gave only moderate yields [18]. Very recently, Journal of Fluorine Chemistry 125 (2004) Dolbier and co-workers reported several high yielding CeCl 3 catalyzed Reformatsky reactions of ethyl bromofluoro acetate with aldehydes and ketones [19].…”
Section: Synthesis By C-c Bond Formation Of Partially Fluorinated Buimentioning
confidence: 99%
“…In sharp contrast, reactions between metal enolates of fluoroacetate derivatives general exhibit poor stereoselectivity. [18,19] Although aldolases had previously been shown to accept substrates with remote fluorine atoms, [20,21] …”
Section: Introductionmentioning
confidence: 99%